Prostatic Artery Embolization for Benign Prostatic Hyperplasia—A Primer for Interventional Radiologists - Bilhim, Tiago; Costa, Nuno V.; Torres, Daniel (The Arab Journal of Interventional Radiology, 2021)
Male patients over 50 years with lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH) are potential candidates for prostatic artery embolization (PAE). PAE is not a perfect fit for all BPH patients. Careful pre- and postpostprocedural evaluation/consultation with correct selection of patients should be tailored on an individual basis. Evaluated parameters include the following: LUTS severity quantification with validated questionnaires as the international prostate symptom score (IPSS) and quality of life (QoL), erectile and ejaculatory evaluation with validated questionnaires, blood tests including full blood count, coagulation profile, renal function and total/free prostate-specific antigen (PSA), prostate volume measured by multiparametric magnetic resonance (mpMR) of the prostate and/or transrectal ultrasound, uroflowmetry measuring the peak urinary flowrate (Qmax), and postvoid residual urine (PVR). Correct arterial anatomy identification with either computed tomography (CT) angiography, MR angiography, or intraprocedural cone-beam CT (CBCT) are suggested for a confident procedure and avoiding potential complications. The minimally invasive nature of PAE with a faster recovery, preserving the sexual function, and comparable results to standard prostatic surgery make the procedure an attractive choice for many male patients suffering with this condition. Patients should be informed about the potential for higher retreatment rates and shorter duration of treatment effect when compared with standard prostatic surgery. In this comprehensive review, we provide an updated toolbox for all interventional radiologists interested in the PAE practice for patients with BPH. We explain how to evaluate patients during consultation before and after PAE, describe the preprocedural imaging required, explain the technique, and narrate how to optimize outcomes. Finally, we review the level of evidence of PAE for BPH.
Keywords: prostatic artery embolization; prostate embolization; benign prostatic hyperplasia; lower urinary tract symptoms